Listening to Javanese Gamelan Can Reduce Depression Score in Institutionalized Elderly - Rochdiat M, Wahyu; Lestari, Elfiana Dewi (Jurnal Keperawatan Soedirman, 2020)
ABSTRACTElderlies who lives in nursing home conceive a high risk of experiencing depression. Music that is usually heard by the elderly in Java Province is Javanese gamelan and there was a few of research that examined its effect on the elderlies depression. The purpose of this study was to assess the impact of listening to Javanese gamelan on the depression score of institutionalized elderly. This research used a quasi-experimental design with a pretest-posttest control group approach. The researchers screened 88 elderlies who live in one of nursing home in Yogyakarta with GDS (Geriatric Depression Scale), which acquired 49 depressed elderlies. A purposive sampling technique (criteria: Javanese, not experiencing the hearing loss, cooperative, and not in an isolation room) conduced 26 elderlies as samples. The subjects were divided into two groups with same proportion of ages in each group. Wilcoxon test indicated that there was a decreasing of the depression score in the intervention group (p-value 0.000). The depression score in the control group increased from 7.46 to 9.46. Javanese gamelan is effective in reducing the depression score in institutionalized elderlies.Keywords: Depression, elderly, Javanese gamelanÂ